Talent identification in elite gymnasts: Why body size is so important - Richards, J. (coachesinfo.com)
Gymnastics has moved over the last 25 years into an era characterised by ahtleticism, agility and small body size. Through the 1970's with Olga Korbut and Nadia Comanichi and into the 80's with Oksana Omilianchik and Mary-Lou Retton, contemporary gymnastics certainly witnessed the 'child champion'. Small and strong; the body shape these athletes had led them to bring the complexity of women's gymnastics to a level never witnessed before.